The effects of a physical activity, nutrition, and body image intervention on girls in intermediate schools in Saudi Arabia - Bahathig, Abeer Ahmad; Abu Saad, Hazizi (Multidisciplinary Digital Publishing Institute, 2022)
Background: This cluster-randomized study aimed to evaluate the effects of an intervention focused on physical activity, nutrition, and body image perception among girls in intermediate schools in Saudi Arabia. A seminar was delivered to the mothers of the girls in the experimental group. The experimental group then attended six interactive sessions within 3 months featuring physical activity, nutrition, and body image perception, followed by a 3-month follow-up period. A total of 138 respondents (68 in the experimental group and 70 in the control group) completed the intervention. Each participant’s body mass index-for-age z-score and waist circumference were measured, and they completed a physical activity, sedentary behavior, and body image perception questionnaires before and after the intervention and at the follow-up. The intervention was evaluated using within- and between-groups generalized estimating equations. There were no significant changes in the respondents’ body mass index-for-age z-score or waist circumference (p > 0.05). However, immediate significant improvements were seen in physical activity, sedentary behavior, and body image satisfaction among the experimental group, and these improvements remained at follow-up (p < 0.001). These differences were more significant among the experimental group than among the control group. We found this intervention effective. Future studies can adapt this intervention for adolescent boys and extend its duration to improve the body mass index outcome.